Junie B. Jones has a peep in her pocket - Park, Barbara; Brunkus, Denise (New York : Random House, 2000)
When Junie B. learns that her kindergarten class is going on a field trip to a farm, she worries about being attacked by a rooster.
"A Stepping Stone book."
2.1.
006-009.
360
Keywords: School field trips -- Fiction; Farms -- Fiction; Fear -- Fiction